KADAR KOLESTEROL HEPAR AYAM BROILER SETELAH PEMBERIAN TEH KOMBUCHA - Muliani, Hirawati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
This research is aimed  to know the effect of kombucha tea on liver cholesterol level of broiler chickens. Twenty four female broiler chickens  were acclimated during 3 weeks and then allotted into 4 groups, each group was treated as follows : P0 = control, without combucha tea, P1= water + 10% kombucha tea, P2 = water + 20% kombucha tea, P3 = water + 40% kombucha tea.  The kombucha tea has been fermented during 12 days at 250 C. Long of treatment was 32 days . Replications was 6 times. Parameters observed were liver cholesterol level, body weight, and drink consumption. Data was analyzed  by varians analysis with Completely Random Design and Least Significant Difference. The result of the research was given of combucha tea can reduce liver cholesterol level significantly for broiler chickens.   Keywords : liver cholesterol, kombucha tea, broiler chickens.